Bone Mineral Density (BMD) Status and its Determinants in Rural Women of Reproductive Age - Rakhshanda Toheed , Talha Bin Ayub, Irum Munawwar , Saba Mumtaz ,Gulfreen Waheed (Journal of Rawalpindi Medical College, 2016)
Background: To determine the prevalence of low bone mineral density (BMD) and its main determinants in rural women of reproductive age. Methods: In this cross sectional study women attending antenatal clinic/ gynae OPD belonging to reproductive age (15-45 years) were included. Those menopausal, taking steroids, having hyperthyroidism, Cushing’s disease were excluded. Age of all patients, weight/height(BMI), socio-economic status, education, working/non working, pregnancy, parity, intake of milk and milk products, exposure to sun light, smoking, were noted. Calcaneal quantitative sonometry was used to measure Z-score. Criteria for pre-menopausal women for low BMD/osteoporosis was used. Results: Out of 425 women, 58.9 % had low BMD/ osteoporosis; out of them 50.1 % had low BMD or osteopenia, and 8% had osteoporosis. Mean age was 26.68 + 6.79 years, minimum age 15 years, maximum age 45 years; 89.0 % were having income < 15,000/- monthly. Out of all determinants mentioned above, poor socio-economic status and low intake of milk and milk products were statistically significantly associated with low BMD/osteoporosis. Conclusion: More than half of the women had either low BMD or osteoporosis. Low intake of milk and milk products and poor socio-economic status were mainly significant determinants.